A Study on the Energy Load Evaluation according to the Installation of Multistory Facade and Exterior Shading Device - Lee, Jun-Gi; Kim, Sung-Hoon; Lee, Kyung-Hee (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this research is to get a better plan to reduce the energy used for heating and cooling as a result of thermal energy loss in curtain wall buildings. Methods/Statistical analysis: In order to achieve this goal, the study executed a building energy simulation to evaluate the factors that from a double skin faÃ§ade and curtain wall building. The factors that were considered in this study are the air gap distance of the double skin faÃ§ade, the area ratio of the inner window, the direction of the building and the shading device conditions. The results of this study are based on the weather data of Busan input in DesignBuilder. Findings: When the inner window area ratio was installed at 40% without the double skin faÃ§ade, the energy load reduction effect was better with the exterior shading device at South-45Â°-West and South. With the double skin faÃ§ade, the energy load reduction effect was better without the exterior shading device in West, South-45Â°-East and East. When the inner envelope window area ratio was installed at 70% and 100% the, the energy load reduction effect was better with the exterior shading device in all direction. Improvements/Applications: The optimal double-skin design study will be carried out by adjusting the installation location and angle schedule of the shading device after the orientation. Â Â